Targeting the JAK2V617F mutant hematopoietic microenvironment in myeloproliferative neoplasm - Yeware, Amar (Frontiers in Hematology, 2026)
The acquired JAK2V617F mutation is predominantly detected in hematopoietic stem cells(HSCs), leading to myeloproliferative neoplasms(MPN). Emerging evidence shows that JAK2V617F bearing cells remodel their microenvironment by dysregulating cytokines, and altering adhesion molecules, with histopathological changes in the spleen and liver that influence thrombosis and disease progression. However, how JAK2V617F bearing cells interact with and modify niche factors to promote MPN progression remains insufficiently defined and represents an important therapeutic opportunity. This review focuses on the effect of mutant HSCs on the BM niche, emphasizing key signaling pathways such as IL-β1, TPO/MPL, TGF-β1, VEGF, CXCR4/CXCL12, and altered metabolism. Understanding these dysregulated interactions provides a rationale for therapies that directly target the niche components. Current therapies, including JAK inhibitors, partially address symptoms but are limited by resistance and off-target effects, whereas emerging niche-directed strategies such as such as CXCR4 antagonists, TGF-β1 blockers and metabolic modulators, may restore normal hematopoiesis and overcome ruxolitinib resistance. Therefore, understanding and modulating these HSC-niche interactions advances a path toward durable and transformative therapies for MPNs.